Prevalence and associated factors of caesarean section delivery: analysis from the Nepal Demographic and Health Survey 2022 - Sudesh Pandit; Om Chandra Thasineku; Sujan Karki; Sushil Sharma (BMJ Open)
Objective Ensuring equitable access to emergency obstetric care is essential for reducing maternal mortality. This study examines the prevalence and associated factors of caesarean section (CS) delivery in Nepal during 2022.Design This study used secondary data from the 2022 Nepal Demographic and Health Survey (NDHS) for the analysis, employing stratified two-stage cluster sampling. The sample comprised 1977 live births from women aged 15–49 years, with CS delivery serving as the outcome variable. Independent variables were categorised into residency, socio-economic, maternal health service and maternal factors. Binary logistic regression was applied to estimate crude and adjusted odds ratios (AORs) for associations, with statistical significance assessed at p<0.05. A complex sample analysis was performed to account for the stratified survey design.Setting Nepal.Participants This study included 1977 live births from mothers who delivered within the 2 years preceding the survey, representing women aged 15–49.Outcome variable CS delivery.Results The study analysed factors associated with CS delivery in Nepal using NDHS 2022 data. Rural residence (AOR: 0.581; p<0.001) and regional disparities, particularly in Terai (AOR: 2.651; p<0.05), significantly influenced CS delivery rates. Higher maternal education (AOR: 3.207; p<0.01) and wealth index (richest quintile AOR: 6.729; p<0.001) were associated with increased odds of CS delivery. Delivery in private institutions (AOR: 5.862; p<0.001) and maternal age (35–49 years AOR: 6.151; p<0.001) showed strong associations, while higher birth orders reduced the probability of CS.Conclusion The factors influencing CS rates in Nepal include socio-economic status, maternal education, geographical region and access to maternal health services. Regional disparities and the rising prevalence of CS underscore the necessity for equitable healthcare resource allocation and the implementation of need-based approaches and clear, evidence-based guidelines to ensure the appropriate use of CS for improving maternal and child health outcomes.